Perencanaan Dan Penerapan Laporan Keuangan Berdasarkan Psak 45, Guna Mencapai Financial Freedom Pada Yayasan Al - Kamilah - Mubarok, Ikhsan; Ningrum, Alieffia Farda; Destiani, Anisya Restu; Handayani, Morelia Nurul; Yohanes, Yohanes (Universitas Pamulang, 2021)
In the current era in Indonesia, there are still many non-profit organizations that do not pay attention to even not prioritizing how to prepare a good financial reporting system in accordance with existing accounting standards in this country. Organizations still prioritize the excellence of the social programs they run. We know that financial statements are very important documents containing the financial records of a company or organization in a certain period. Of course, financial reports should be a medium for evaluating the performance of a company or organization. This occurs due to several factors, lack of socialization and training related to Statementqqof FinancialqqAccountingqqStandards (PSAK) No. 45, or because the organizationqis indifferent and tends to be lazy in applying financial statements based on these principles. If the organization has implemented reports in accordance with proper accounting standards, it will give a fair predicate without permission and then achieve financial freedom (Financial Freedom) in the future. The purpose of this researchqis toqplan andqpresent a financial report at the Al - Kamilah Foundation so that the financial statements do not only contain cash receipts and disbursements but also apply PSAK No. 45. This research provides solutions, directions, and recommendations for financial reports. achieve financial freedom in a non-profit organization. This research uses descriptive - qualitative methods by collecting data, analyzing the data that will be used to see clarity of the problem under study. The substance of vocational skills learning is in the form of practical skills training and is carried out as a simulation of financial report budgeting. The technique uses field survey data by visiting the Al - Kamilah Foundation, interviews, and literature studies. Keywords: Financial Report; PSAK No. 45; Financial Freedom